ANALISIS PENERIMAAN DAN PENGGUNAAN TEKNOLOGI (UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY) TUTORIAL ONLINE MAHASISWA PROGRAM S1 PGSD DAN S1 PGPAUD UNIVERSITAS TERBUKA - Irawan, Windra; Asiah, Nur; Tuliabu, Mody Gayes (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
The online  tutorials for undergraduatestudents at Universitas Terbuka has 30% of contributions to the grade of the final exam, which is why students are expected not to depend solely on independent learning without any supporting facilities. With 339 undergraduate students of SIPAS NON-TTM PGSD and PGPAUD, the researcher used the unified theories of acceptance and use of technology to analyze students acceptance and technology usage, and using multiple regression as the statistical tools to test out the influence of performace expectancy, effort expectancy, social influence, and facilitating conditions towards the behavioral intention of undergraduate students of PGSD and PGPAUD in using online  tutorials.It was found that facilitating conditions had the most significant influence towards behavioral intention, while performance expectancy was right after. Lower influence was found in social influence, while the effort expectancy doesn't have any significant effect on behavioral intention of undergraduate students of PGSD and PGPAUD in using online  tutroials.